LIGHT CHAIN AMILOYDOSIS (AL) – CLINICAL, LABORATORY CHARACTERISTICS AND TREATMENT APPROACH - Stanković, Ana; Lazarević, Milana; Srdić, Sara; Sretenović, Aleksandra (Medicinski podmladak, 2021)
Introduction: Light chain (AL) amyloidosis is a plasma cell neoplasia characterized by deposition of a pathological insoluble fibrillary protein, i.e light chain immunoglobulin.Aim: To show clinical and laboratory characteristics of patients, course, treatment modalties, prognose.Material and methods: 30 newly diagnosed patients with AL amyloidosis were analyzed. Histopathologicaldiagnosis was made by identifying Congo red positive deposits in the affected organs.Results: 30 patients (pts) were analyzed, 21male/9female, average age 59 years. Paraprotein was found in 26 (86.7%). The most frequent monoclonal protein was imunoglobulin light chain (14pts, 46.7%), Lambda isotype was more common (21pts, 70%). Organ involvement: heart (21pts, 70%), kidney (21pts, 70%), subcutis (18pts, 60%), bone marrow (12pts, 40%), liver (7pts, 23.3%) and 9pts (30%) had unusual localization (lung, skin, uterus); 18pts (60%) had more than one parenchimal organ involved. Biomarkers of cardiac involvement: BNP in 8pts (26.7%) NT- proBNP in 13pts (43.3%), troponin 7pts (23.3). Elevation of LDH was found in 7pts (23.3%). Anemia was observed in 3 (10%) and trombocitopenia in 1 pts (3.3%). With conventional chemiotherapy were treated 21pts (70%), bortezomib was applied in 9pts (30%). With ASCT was performed on 2pts (6.7%). Overall treatment response (ORR, ≥PR) was achived in 21pts (70%). All pts treated with bortezomib based HT had treatment response (≥PR). In transplant ineligible pts, treatment modality did not affect PFS (Log Rank=1.675, p=0.196), but showed statistically significant affect on OS (Log Rank=3.834, p=0.05). Number of parenhimal organ involvement (1vs.≥2) did not show influence neither of PFS or OS (PFS:Log Rank=0.017, p=0.895; OS:Log Rank=0.739, p=0.390). Although the most important negative prognostic factor, cardiac involvement had no affect on OS (Log Rank=2.480, p=1.410).Conclusion: Early recognition of disease and avoidance of organ involvement is essential importance for the course of disease and treatment outcome. Bortezomib based protocols and HDT with ASCT are essential for maintaining long-term remission and improving OS. Keywords:Amyloidosis,Treatment,Prognosis
Keywords: Amyloidosis; treatment; prognosis